PRIMER REGISTRO DEL CANGREJO PILUMNUS PANNOSUS RATHBUN (DECAPODA: BRACHYURA: PILUMNIDAE) PARA EL CARIBE COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
This paper reports Pilumnus pannosus Rathbun, a member of the family Pilumnidae, for the first time from the Colombian Caribbean. This report is based on specimens collected on the continental shelf of the Guajira Peninsula, where the species was found associated with seagrass meadows of Thalassia testudinum.